RAD-Seq-Based High-Density Linkage Maps Construction and Quantitative Trait Loci Mapping of Flowering Time Trait in Alfalfa (Medicago sativa L.) - Jiang, Xueqian; Yang, Tianhui; Zhang, Fan; Yang, Xijiang; Yang, Changfu; He, Fei; Long, Ruicai; Gao, Ting; Jiang, Yiwei; Yang, Qingchuan; Wang, Zhen; Kang, Junmei (Frontiers in Plant Science, 2022)
Alfalfa (Medicago sativa L.) is a perennial forage crop known as the “Queen of Forages”. To dissect the genetic mechanism of flowering time (FT) in alfalfa, the high‐density linkage maps were constructed with an F1 mapping population derived from a cross between Cangzhou (P1) and ZhongmuNO.1 (P2), consisting of 150 progenies. The FT showed a transgressive segregation pattern in the mapping population. A total of 13,773 single-nucleotide polymorphism markers were obtained by using restriction-site associated DNA sequencing and distributed on 64 linkage groups, with a total length of 3780.49 and 4113.45 cM and an average marker interval of 0.58 and 0.59 cM for P1 and P2 parent, respectively. Quantitative trait loci (QTL) analyses were performed using least square means of each year as well as best linear unbiased prediction values across four years. Sixteen QTLs for FT were detected for P1 and 22 QTLs for P2, accounting for 1.40 to 16.04 % of FT variation. RNA-Seq analysis at three flowering stages identified 5039, 7058 and 7996 genes that were differentially expressed between two parents, respectively. According to QTL mapping, DEGs analysis, and functional annotation, seven candidate genes associated with flowering time were finally detected. The important QTLs identified in this study could be used for further implementing marker‐assisted selection, and further identification of the candidates would provide insights into genetic control of FT in alfalfa.